2014
DOI: 10.1097/ogx.0000000000000121
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Interventions, Lifestyle Changes, and Dietary Supplements in Preventing Gestational Diabetes Mellitus

Abstract: Gestational diabetes mellitus (GDM) is associated with increased rates of fetal morbidity and mortality, both during the pregnancy and in the postnatal life. Current treatment of GDM includes diet with or without medications, but this management is expensive and poorly cost-effective for the health care systems. Strategies to prevent such condition would be preferable with respect to its treatment. The aim of this literature review was to evaluate studies reporting the efficacy of the most used approaches to p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
20
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 69 publications
1
20
0
1
Order By: Relevance
“…Study findings summarized in systematic reviews and meta-analyses are diverse but suggest a beneficial effect (9,10,13,30). Additional research is needed because of the differences in interventions examined (e.g., diet quality, energy restriction, provision of fortified food products, dietary counseling) as well as the heterogeneous study populations and GDM diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Study findings summarized in systematic reviews and meta-analyses are diverse but suggest a beneficial effect (9,10,13,30). Additional research is needed because of the differences in interventions examined (e.g., diet quality, energy restriction, provision of fortified food products, dietary counseling) as well as the heterogeneous study populations and GDM diagnostic criteria.…”
Section: Discussionmentioning
confidence: 99%
“…Intervention studies were not included because results from these studies have been systematically reviewed (9,10,13).…”
Section: Study Selectionmentioning
confidence: 99%
“…Initial treatment of GDM involves dietary modification, lifestyle changes, moderate exercise and dietary supplements (Asemi et al, 2013;Facchinetti et al, 2014). Recently, zinc supplementation has been proposed for decreased insulin resistance and lipid profiles in patients without GDM.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have also shown the pathological involvement of the immune system in type 2 diabetes, that is, based on the presence of autoantibodies against β cells, self-reactive T cells and evidence of beneficial effect of some anti-inflammatory and immunomodulatory therapy, being viewed as an autoinflammatory disease (Itariu and Stulnig, 2014). Nutritional interventions with food supplements as a form of complementary therapy in patients with diabetes are being used increasingly to counter these effects (Shane-McWhorter, 2005; Campbell, 2010; Ho et al, 2013; Facchinetti et al, 2014). In this review, botanicals that are most frequently promoted to help manage blood glucose levels and can be found marketed as food supplements promoting antidiabetic activity were selected and their mechanism of action described.…”
Section: Introductionmentioning
confidence: 99%